How Industrial Dispute Problems Are Resolved in Indonesia? A Book Review Penyelesaian Sengketa Hubungan Industrial, Ari Hermawan, UII Press, 142 Pages, ISBN 978-602-6215-56-7 - Samuel, Gerald (Universitas Negeri Semarang, 2020)
In the explanation of industrial relations, it was explained that there were three parties involved in it, including workers, employers and the government. Each component has a different function. The Government in Industrial Relations has the function of establishing policies, providing services, carrying out supervision and other matters relating to the neutrality of the workers and employers. Workers themselves have the function of carrying out work in accordance with obligations, order for the sake of sustainable production, advancing the company. Whereas employers within the scope of Industrial Relations have the function of creating partnerships, developing businesses, expanding employment opportunities, and providing workers' welfare openly.